The Influence Of Internal Control And The Use Of Information Technology On Sales Effectiveness (Empirical Study Of Plasa Telkom Sumedang) - Risna Nurhayati (LPPM Universitas Sebelas April, 2023)
This study aims to determine the effect of internal control and the use of information technology on sales effectiveness at Plaza Telkom Sumedang. Sampling by simple random sampling method as many as 68 respondents. Data collection techniques using observation methods and distributing questionnaires to respondents. Technical data analysis using SPSS 25. The method of analysis used is multiple linear regression method, analysis of the correlation coefficient, analysis of the coefficient of determination, and hypothesis testing. The results of the ttest regarding the effect of internal control on sales effectiveness show that there is a positive and significant effect with a tcount=3.870>ttable=1.996. Meanwhile, regarding the influence of the use of information technology on sales effectiveness, it shows that there is a positive and significant effect with tcount=5.487>ttable=1.996. The results of the Ftest show that fcount=37.918>ftable=3.14, thus together internal control and the use of information technology have a positive and significant influence on sales effectiveness at Plasa Telkom Sumedang. The results of the determination test, internal control and the use of information technology have an effect of 53.8% on sales effectiveness at Plasa Telkom Sumedang, and 46.2% are influenced by other factors that are not included in the research variables.